Cara Praktis Penyusunan Perangkat Ktsp Berdasarkan Nilai-Nilai Karakter Bangsa - Ghufron, Anik (Literasi: Jurnal Ilmu Pendidikan, 2012)
The curriculum is one important component of education which affects the quality of our educational output. Value education that is currently emerged by education expert should be appreciated and implemented in the use of curriculum development. In this paper writer explores the way developing a character education curriculum based on national curriculum. Curriculum development is started from plan, actuating and evaluation, it represent series of instruction management. Development of the curriculum based on the values of the character's personality allows learners to develop optimally in learning activities.Key words: Curriculum, value education, character